2007
DOI: 10.1295/polymj.pj2007090
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hyperbranched Polymer with Degree of Branching of Approximately 100% by Polycondensation of 2-(4-Phenoxyphenoxy)fluorenone

Abstract: ABSTRACT:An approximately 100% branched hyperbranched polymer was successfully prepared using 2-(4-phenoxyphenoxy)fluorenone as a monomer in an acidic medium. The kinetics of the model reaction between 9-fluorenone and anisole was investigated. The reaction obeyed the second-order kinetics, indicating that the first reaction, i.e., the formation of the intermediate from 9-fluorenone and anisole, is considerably slower than the second one, i.e., the reaction of the intermediate with anisole. Based on this findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…16) (45). A kinetic study clarified that the reaction obeyed second-order kinetics, in which the first reaction, which is the formation of the intermediate from 9-fluorenone and 3mercaptopropionic acid, is considerably slower than the second one, which is the reaction of the intermediate with 3-mercaptopropionic acid.…”
Section: Controlled Degree Of Branch In Hyperbranched Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…16) (45). A kinetic study clarified that the reaction obeyed second-order kinetics, in which the first reaction, which is the formation of the intermediate from 9-fluorenone and 3mercaptopropionic acid, is considerably slower than the second one, which is the reaction of the intermediate with 3-mercaptopropionic acid.…”
Section: Controlled Degree Of Branch In Hyperbranched Polymermentioning
confidence: 99%
“…Based on the model reaction, a hyperbranched poly(thioketal) with 100% DB was successfully prepared using 2-[4-(4-mercaptobutoxy)phenoxy]-9H-fluoren-9one as an AB 2 monomer in trifluoroacetic acid, in which the A and B 2 functionalities correspond to the thiol and 9-fluorenone groups, respectively (Fig. 17) (45).…”
Section: Controlled Degree Of Branch In Hyperbranched Polymermentioning
confidence: 99%
“…Thus, the model reaction between 9-fluorenone (1) and anisole (2) was first investigated in the presence of MPA in trifluoroacetic acid. 67 The reaction between 1 and 2 (0.80 equivalent) was conducted at 60 1C for 20 h in the presence of 3 mol% MPA. Figure 5 illustrates the changes in the consumption of 1 and 2 and the yield of the diarylated product of 3 with time, as determined by 1 H-NMR.…”
Section: Use Of Fluorenone Compoundsmentioning
confidence: 99%
“…67 Synthesis of HBPs T Higashihara et al static effects (Scheme 17). [82][83][84] Furthermore, when an alcohol intermediate is formed in an acidic solution, it will rapidly react with another aromatic compound to yield a diarylated product.…”
Section: Meomentioning
confidence: 99%
“…Ueda et al 13 reported on the synthesis of a HBP, with an approximately 100% degree of branching, by the polycondensation of 2-(4-phenoxyphenoxy)fluorenone. We examined [14][15][16] the synthesis of hyperbranched polyester (HBPE) epoxy resins containing methacryloyl groups (HBPE(ep)-MA), hyperbranched oxetane resin containing methacryloyl groups (HBPE(ox)-MA) and hyperbranched polyurethane containing methacryloyl groups (HBPU-MA) by the reaction of an A 2 -type monomer with a B 3 -type monomer and their photoinduced radical polymerization.…”
Section: Introductionmentioning
confidence: 99%